Educational Ideology in Character Building Through National Songs at Anak Soleh Mandiri Integrated Islamic Elementary School Banjarmasin (Universitas Negeri Semarang, 2023)
This research was conducted at Anak Soleh Mandiri Integrated Islamic Elementary School Banjarmasin. The aim of this research is to discover the instilling of students’ character values through national songs and applied educational ideology. Educational ideology may affect the ongoing educational process, so it eventually affects the educational outcomes. This research is based on the reality of public elementary schools and integrated Islamic elementary schools in instilling students’a character values through national songs, using different methods, techniques, and ideologies. It influences the choice of educational ideology applied in the school. This research is qualitative research since it describes the problem in a descriptive narrative. The data collection utilized the techniques of observation, interview, and documentation. The data analysis process was carried out using qualitative analysis, and triangulation is used to check the validity of the data. The results of the research are: (1) The characters instilled at Anak Soleh Mandiri Integrated Islamic Elementary School Banjarmasin through national songs include religious, honest, tolerant, disciplined, hard work, creative, independent, democratic, curiosity, nationalistic, patriotic, appreciating achievement, friendly, communicative, peace-loving, fond of reading, caring for the environment, caring for others, and responsible. (2) The educational ideology used in instilling the students’ character values at Anak Soleh Mandiri Integrated Islamic Elementary School Banjarmasin is conservatism.